THE INFLUENCE OF GDP, INFLATION, AND DEPOSIT RATES ON FDI IN INDONESIA - Fahmi, Anisa Ulul; Septiani, Yustirania (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Foreign Direct Investment (FDI) plays a very important role in providing capital and overcoming the problem of limited funds owned by developing countries in carrying out the economic development process. This study aims to analyze the effect of Gross Domestic Product (GDP), inflation, and deposit rates on foreign direct investment (FDI) in Indonesia in the long and short term. The method used in this study is the Autoregressive Distributed Lag (ARDL) method with periodic secondary data (time series) from the early 1990s to 2020. The results obtained in this study indicate that there is a positive and significant effect between GDP on investment foreign direct (FDI). However, inflation shows a negative effect in the long term on foreign direct investment (FDI). Meanwhile, the deposit interest rate in the long term shows a negative effect and in the short term it shows a positive and significant effect on foreign direct investment (FDI).